2018
DOI: 10.1097/ncm.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Data

Abstract: Purpose:The purpose of this study was to explore the difference in maximal lifting capability between 2 modes of lifting (traditional crate and XRTS Lever Arm) over multiple days. The differences in absolute strength values were compared with existing criteria for sincere effort during distraction-based lifting. In addition, rate of perceived exertion (RPE) is presented for the 2 modes of lifting on each day.Primary Practice Setting:Workers' compensation.Methodology and Sample:Forty-four subjects between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These methods include isometric lift testing, visual estimation of effort, and grip and pinch testing along with physiologic measures (30,31,33,34,36,40). By stark contrast, there is a highly accurate method that uses repeated trials in conjunction with the component of distraction (31,32,38,39). This method assesses reproducibility with the same activity under 2 different conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods include isometric lift testing, visual estimation of effort, and grip and pinch testing along with physiologic measures (30,31,33,34,36,40). By stark contrast, there is a highly accurate method that uses repeated trials in conjunction with the component of distraction (31,32,38,39). This method assesses reproducibility with the same activity under 2 different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated an average error in visually estimating the load of 43.0% (35). In control studies, subjects assigned to give maximal effort lifting have been measured with 100% specificity (38,39).…”
Section: Introductionmentioning
confidence: 99%